Smart Contracts in Non-Fungible Token Transactions Using Cryptocurrency (Case Study on Ghozali Everyday) - Anissa Nabilla; Suherman Suherman (Universitas Islam Sultan Agung, 2025)
The development of blockchain technology has given rise to new innovations in the form of smart contracts, which are widely used in digital asset transactions, including Non-Fungible Tokens (NFTs). One case that highlights this phenomenon is Ghozali Everyday, where smart contracts play a crucial role in regulating the buying and selling of NFTs. However, the implementation of smart contracts in Indonesia faces legal challenges, particularly regarding the use of cryptocurrency as a payment instrument, which is still prohibited by Bank Indonesia regulations, even though electronic contracts are recognized as valid by the ITE Law. This study uses a normative juridical method with a legislative and conceptual approach. The analysis is conducted using Hans Kelsen's Hierarchy of Norms theory and Gustav Radbruch's Legal Validity theory to assess legal certainty, fairness, and utility in regulating smart contracts and cryptocurrencies in Indonesia. The results show a conflict of norms that creates legal uncertainty and limited legal protection for digital asset transaction actors. Therefore, regulatory updates are needed that are adaptive, consistent with the hierarchy of laws and regulations, and provide more comprehensive protection for consumers and businesses.